1999
DOI: 10.1136/sti.75.5.312
|View full text |Cite
|
Sign up to set email alerts
|

Risk factors for the acquisition of genital warts: are condoms protective?

Abstract: Objectives: To characterise risk factors for the acquisition of genital warts and specifically to determine whether condoms confer protection from infection. Methods: A retrospective case-control study comparing demographic, behavioural, and sexual factors in men and women with and without newly diagnosed genital warts, who attended Sydney Sexual Health Centre (SSHC), an inner city public sexual health centre, in 1996. Data were extracted from the SSHC database. Crude odds ratios (OR) were calculated to compar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

10
50
3
4

Year Published

2001
2001
2024
2024

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 92 publications
(67 citation statements)
references
References 18 publications
10
50
3
4
Order By: Relevance
“…Only a few studies were performed in men and reported that consistent condom use reduced the risk for genital warts or subclinical HPV infection (Hippelainen M et al, 1993a;Wen et al, 1999). Of interest is the work of Hippelainen MI et al (1994) who found that condom use had a positive effect on the cure rate of genital HPV lesions in male partners of HPV-infected women.…”
Section: Discussionmentioning
confidence: 99%
“…Only a few studies were performed in men and reported that consistent condom use reduced the risk for genital warts or subclinical HPV infection (Hippelainen M et al, 1993a;Wen et al, 1999). Of interest is the work of Hippelainen MI et al (1994) who found that condom use had a positive effect on the cure rate of genital HPV lesions in male partners of HPV-infected women.…”
Section: Discussionmentioning
confidence: 99%
“…This presumably implies different transmission modes and dynamics for HPV-6, HPV-11 and HPV-16 infections. HPV-16 is predominantly transmitted by mucosal contacts, while HPV-6 and HPV-11 are also transmitted via the skin (Wen et al, 1999). Finally, possible competitive advantages favouring the spread of HPV-16 over HPV-6 and HPV-11 or chance cannot be ruled out as explanations for the observed differences between the oncogenic and non-oncogenic HPV types.…”
mentioning
confidence: 99%
“…89 Overall, condoms appear to offer minimal protection against incident infection with HPV but greater protection against progression to disease (warts or intraepithelial lesions). [89][90][91] Two studies have shown more rapid resolution of clinically defined HPV lesions in both males and females with consistent condom use, 92,93 and Shew et al 94 found reduced duration of infection with condom use in women. Thus, if condoms reduce the time taken for resolution of HPVassociated lesions, they may also indirectly reduce onward transmission.…”
Section: Are Circumcision and Condoms Protective Against Infection?mentioning
confidence: 99%